DEVELOPMENT OF CHILDREN'S ATTITUDE AND BEHAVIOR THROUGH SPORTS AND PHYSICAL EDUCATION - Permana, Gilang (ASEAN Journal of Sport for Development and Peace, 2024)
This article investigates the development of children's attitudes and behaviour through the use of sport and physical education learning. By analyzing various related studies, we explore the significant role of sport in shaping character, leadership, cooperation and discipline in children. The literature review method is used to investigate empirical studies, theoretical reviews, and other related concepts in the relevant literature. A PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) design was adapted to identify, screen, and synthesize articles relevant to this topic. The results show that sports and physical education significantly positively impact the development of children's attitudes and behaviour. These findings' practical and theoretical implications are discussed to guide educators and policy makers in strengthening positive aspects of child development.